Insights into the Elder Care Conundrum through complementary use of SSM and TOC - Mabin, Vicky; Sommer, Kim (School of Management Working Papers, 2011)
Whether a parent should move into an assisted care facility can be a difficult decision for families and one that is increasingly evident as the „baby-boomer‟ population ages. This paper explores decisions about how best to care for elderly family members and in particular, whether a parent should move (or be moved) into an assisted care facility (ACF). The problematic situation is described as based on personal experience of the first author initially. Two complementary lenses were then employed as problem structuring aids, providing critical insights into the dilemma facing family members. A Soft Systems Methodology (SSM) was used first, followed by the Evaporating Cloud (EC) method from the Theory of Constraints. This use of complementary lenses in multimethodological fashion allowed the elicitation, clarification and elaboration of assumptions underlying the issue of whether the parent should go into an ACF. As a result, multiple avenues for resolving the issue are surfaced, along with several opportunities for further research. This paper contributes to Community OR by this case study showing how the different frames can work to address the fraught situation in which families can find themselves, as they seek to safeguard their elderly parents by accessing ACF, while also endeavouring to maintain satisfactory family relationships. The paper makes a unique contribution, not just in terms of highlighting the elder care situation and suggesting ways forward, but also in terms of the multi-methodological use of SSM and TOC. Finally, it is significant that the case study arose from the use of SSM in the USA, where such „Soft OR‟ methods are rarely applied.